2009
DOI: 10.1177/0741932508327465
|View full text |Cite
|
Sign up to set email alerts
|

Do Special Education Interventions Improve Learning of Secondary Content? A Meta-Analysis

Abstract: The authors describe findings from a research synthesis on content area instruction for students with disabilities. Seventy studies were identified from a comprehensive literature search, examined, and coded for a number of variables, including weighted standardized mean-difference effect sizes. More than 2,400 students were participants in these investigations. Studies included interventions involving content areas, such as science, social studies, and English, and employed a number of different interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 71 publications
(30 reference statements)
2
117
1
1
Order By: Relevance
“…Several spatial and graphic organizers (such as concept maps, concept diagrams, visual aids, semantic maps, semantic feature analysis, etc.) have an overall positive effect on learning science, especially for students that encounter difficulties in writing, in understanding the content of science, and in constructing and refining cognitive schemata (See also Scruggs et al, 1998 andScruggs et al, 2010.) The contribution of the graphic organizers to the retaining of information, knowledge and skills compared to the independent or guided study of a text has been also investigated.…”
Section: Multiple Means Of Representation and Graphic Organizersmentioning
confidence: 99%
See 3 more Smart Citations
“…Several spatial and graphic organizers (such as concept maps, concept diagrams, visual aids, semantic maps, semantic feature analysis, etc.) have an overall positive effect on learning science, especially for students that encounter difficulties in writing, in understanding the content of science, and in constructing and refining cognitive schemata (See also Scruggs et al, 1998 andScruggs et al, 2010.) The contribution of the graphic organizers to the retaining of information, knowledge and skills compared to the independent or guided study of a text has been also investigated.…”
Section: Multiple Means Of Representation and Graphic Organizersmentioning
confidence: 99%
“…Hands-on activities are generally more effective when they are part of well-structured teaching, which is circumscribed by rules and specific science concepts. Scruggs et al (2010) mention that systematic presentation of rules through examples and repetition, followed by guided practice immediately after the completion of each part of the lesson is beneficial for students in comparison with the ones that gradually get grasp of a rule via exploratory learning and constructivism. Moreover, LD students get a better understanding of science concepts when they are engaged into inquiry-based instruction without activities rather than instruction based on unstructured activities.…”
Section: Constructivism Exploratory Learning Hands-on Activities Cmentioning
confidence: 99%
See 2 more Smart Citations
“…The classroom teacher also applied findings from research on teaching secondary school content to students with learning disabilities. A meta-analysis of special education interventions for secondary content area learning (Scruggs, Mastropieri, Berkeley, & Graetz, 2010) found that computer-assisted instruction and hands-on activities were effective in increasing content area knowledge for students with learning disabilities. In a review of empirical studies of evidence-based strategies for instruction of older students with learning disabilities, Roberts, Torgesen, Boardman, and Scammacca (2008) concluded that a lack of motivation adversely affects adolescents' abilities to enhance vocabulary and reading comprehension skills.…”
Section: The Current Studymentioning
confidence: 99%